2016
DOI: 10.1177/0003489416629162
|View full text |Cite
|
Sign up to set email alerts
|

Improved Gustatory Sensitivity in Morbidly Obese Patients After Laparoscopic Sleeve Gastrectomy

Abstract: In this study, we were able to show the significant improvement in gustatory sensitivity of morbidly obese patients after laparoscopic sleeve gastrectomy for the first time in literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 31 publications
4
41
1
Order By: Relevance
“…This interpretation is further corroborated by a recent study, which showed improved sour taste after weight-loss induced by bariatric surgery. 33 Also, our findings of both improvement and decrements in performance are incompatible with learning effects from repeated testing in obese children that would yield generally improved but not decreased performance.…”
Section: Discussioncontrasting
confidence: 62%
“…This interpretation is further corroborated by a recent study, which showed improved sour taste after weight-loss induced by bariatric surgery. 33 Also, our findings of both improvement and decrements in performance are incompatible with learning effects from repeated testing in obese children that would yield generally improved but not decreased performance.…”
Section: Discussioncontrasting
confidence: 62%
“…Previous reports have suggested either no difference on sweet and salty taste sensitivity between obese and lean participants (Bertoli et al, 2014;Pepino et al, 2010;Simchen et al, 2006), or even lower sensitivity in obesity for salty (Skrandies & Zschieschang, 2015) for sour (Bertoli et al, 2014), sour and bitter (Simchen et al, 2006), or for sweet, salty, sour and bitter (Proserpio et al, 2015). An improvement of taste detection rates has also been reported after weight loss (Altun et al, 2016). However, it cannot be excluded that the choice of methods and the resolution of the measure (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…(80,82) An increased taste sensitivity, measured by assessing ability to detect tastes, is seen after bariatric surgery, particularly for sweet and salty stimuli. (83,84) Furthermore, people assign lower hedonic values and reduced liking scores to tastes previously perceived as pleasant. Desire to eat and tendencies toward food-addictive behaviour also decrease following bariatric surgery.…”
Section: Bariatric Surgerymentioning
confidence: 99%